Forensic nurses’ mental well-being in handling cases insights from jean watson’s caring theory: A scoping review - Sudarwati, Sudarwati; Haryanto, Haryanto; Suriadi, Suriadi (JOURNAL OF Mental Health Concerns, 2026)
Background: Forensic nursing is a specialized field of nursing that plays a vital role in handling forensic cases involving both healthcare and legal aspects. In practice, forensic nurses are confronted with complex situations that require strong clinical, emotional, and ethical competencies. Jean Watson’s Theory of Caring is considered a relevant framework to support forensic nurses in delivering holistic and humanistic care. Purpose: To map the existing scientific evidence related to forensic nurses’ experiences in managing forensic cases through the application of Jean Watson’s Theory of Caring. Method: A scoping review was conducted by searching the literature through Google Scholar and PubMed databases. Articles were selected based on predefined inclusion and exclusion criteria, published between 2018 and 2024, and relevant to forensic nurses’ experiences and the application of caring theory. The article selection process followed the PRISMA-ScR guidelines. Results: The findings indicated that the application of Jean Watson’s Theory of Caring in forensic nursing contributes to improved therapeutic relationships, enhanced emotional support, and fulfillment of patients’ holistic needs. The experiences of forensic nurses reflect significant psychological, ethical, and professional challenges; however, these challenges can be managed through the consistent application of a caring approach. Conclusion: Jean Watson’s Theory of Caring plays an important role in forensic nursing practice. This scoping review highlights the need to strengthen forensic nurses’ caring competencies to support care delivery that is grounded in humanistic values and justice. Keywords: Forensic Nursing; Jean Watson Caring Theory; Nurse Experience; Scoping Review.